Budaya Organisasi Work From Anywhere pada Divisi E-Government Procurement PT. Telkom Indonesia - Musfira, Delima Asri; Hariyati, Farida; Agustini, Vilya Dwi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
Communication Culture of Work From Anywhere Workers in the E-Government Procurement Division of PT Telkom Indonesia. Organizational culture is not just about the way messages are delivered, but also delves into values, rituals and communication patterns. But what if organizational culture is applied by workers who rarely meet in the office face-to-face, but only through technology platforms. So how is communication carried out to accommodate the needs of workers who are scattered in various locations. So the purpose of this research is to find out how the WFA organizational culture in the E-Government Procurement Division of PT Telkom Indonesia. The research method used in this research is a case study, with a descriptive qualitative approach. Data collection was carried out by participatory observation, in-depth interviews, and literature review. Meanwhile, the result of this research is that WFA organizational culture in Govtech division is created as through adaptive communication with technology-based, and accentuates the point of ritual assumption based on Organizational Culture theory, because this ritual assumption is only done by employees who work in WFA in Govtech.